Analisis Tingkat Validitas Media E-Book Interaktif Berbasis Augmented Reality (AR) untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 2 Tlanak - Maulidiah, Dhea Hisha; Agustin, Ina (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Technological advances in education have encouraged the emergence of new and creative learning methods to improve student learning progress. One solution that can be implemented is the use of Augmented Reality (AR) technology in learning platforms. AR-based Interactive E-Books offer a more engaging learning experience and have the potential to improve students' focus and understanding. This study aims to measure the validity of AR-based Interactive E-Book media in improving the learning success of fifth-grade students at SDN 2 Tlanak. The method used is Research & Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. This study uses quantitative and qualitative approaches. Quantitative data were obtained from validation sheets filled out by experts in the fields of material, media, and language. The validation results show: (1) material experts gave a score of 84% (very valid); (2) media experts gave a score of 82% (very valid); and (3) language experts gave a score of 80% (valid). Based on these results, the AR-based Interactive E-Book media developed is declared valid and suitable for use as a learning medium. This media has the potential to improve the learning outcomes of fifth grade students at SDN 2 Tlanak.